The Career of Dehumanization towards Cyber Space — An Inglorious Story Vol. 1. - Balassa, Bence (Magyar Rendészet, 2017)
The aim of this short review is to demonstrate some of the important changes and transformations (if there have been any) of bias and hatred led communication and behaviour in the last approximately hundred years in Europe’s mainstream history. What kind of forms and influences of dehumanization are we facing? How, and with what impact has dehumanization thematised common speech? How does its influence define our levels of (in)tolerance? What is the reason behind hate speech and verbal harassment being so easily transferred to Cyber space? How was it possible and what kind of objective reasons are there in the background to make this progress so natural?